Evaluation of 10 SLE susceptibility loci in Asian populations, which were initially identified in European populations - Zhang, Yue-miao (Sci Rep, 2017)
Ten novel loci have been found to be associated with systemic lupus erythematosus (SLE) susceptibility by a recent genome-wide association study conducted in Europeans. To test their disease associations and genetic similarities/differences in Asians and Europeans, we genotyped the 10 novel single nucleotide polymorphisms (SNPs) and performed an association study. A Chinese cohort from Northern China was recruited as the discovery population, and three East Asian cohorts were included for independent replication. The 10 SNPs were genotyped using TaqMan allele discrimination assays. To prioritize the associated SNPs, different layers of the public functional data were integrated. Among the 10 SNPs, rs564799 in IL12A was shared in both ethnicities (P(adjust) = 5.91 × 10(−4); odds ratio = 1.22, 1.10–1.35). We also confirmed the reported polymorphism rs7726414 in TCF7 in the current study (P(adjust) = 4.12 × 10(−8); odds ratio = 1.46, 1.28–1.66). The directions and magnitudes of the allelic effects for most of the 10 SNPs were comparable between Europeans and Asians. However, higher risk allele frequencies and population-attributable risk percentages were observed in Asians than in Europeans. We also identified the most likely functional SNPs at each locus. In conclusion, both genetic similarities and differences across ethnicities have been observed, providing further evidence for a genetic basis of the high incidence of SLE in Asian ancestry.